Clinical Effect of Electroacupuncture on Acute Pancreatitis: Efficacies and Mechanisms - Yu X; Zhu Q (Dove Medical Press, 2023)
Xianqiang Yu,1,2 Qian Zhu3 1Women and Children's Hospital Affiliated to Qingdao University, Qingdao, People's Republic of China; 2University of California, Los Angeles, Department of Cardiology, Los Angeles, CA, USA; 3Department of Hepatobiliary Surgery, Zhongnan Hospital of Wuhan University, Wuhan, People's Republic of ChinaCorrespondence: Qian Zhu, Department of Hepatobiliary and Pancreatic Surgery, Pancreatic Surgery Center, Zhongnan Hospital of Wuhan University, Wuhan, Hubei Province, 430071, People's Republic of China, Email zhuqian@whu.edu.cnAbstract: Acute pancreatitis (AP) is a common acute abdomen and the number one cause of acute digestive hospitalizations in the United States. Abdominal pain is the main clinical manifestation of abdominal symptoms, so reducing the abdominal symptoms caused by inflammation is very important to alleviate the pain of patients. Electroacupuncture (EA) as a traditional Chinese medicine (TCM) therapy has significant conditioning effects on various inflammatory diseases including AP. Continuous studies in recent years have shown that EA conditioning has significant effects on reducing inflammation and regulating gastrointestinal symptoms in AP. At the same time, there is sufficient evidence to further elucidate the mechanism of EA. In this review, we will summarize the effect of EA on AP and its mechanism, so as to better serve clinical practice in the treatment of AP in the future.Keywords: electroacupuncture, acute pancreatitis, traditional Chinese medicine, TCM